Ultimate strength of cracked ship structural elements and systems: A review. (July 2018) - Babazadeh, Ashkan; Khedmati, Mohammad Reza
Abstract: Many ships around the world are getting older. As the ships grow older, more defects such as cracks will come up exposing the ship hull structure to structural failures. Although many investigations have been carried out on the ultimate strength of cracked ship structural elements, there is a gap in design phase of a ship hull structure accurately considering such defects. In particular, available manuscripts by the regulatory bodies simply deal with the repair methods rather than practical design codes and guidelines. Many researchers have employed different methods to investigate ultimate strength of cracked ship structural elements to understand effects of various parameters. But as there is not a benchmark study to be referenced as a standard, sometimes contrasts are observed in the investigations. This paper presents a detailed review on the effects of different crack parameters such as crack length, crack location, crack orientation and gap size, plate thickness, aspect ratio, boundary conditions on the ultimate strength of ship hull elements in a comparative manner to be used as a reference for future investigations. Highlights: Ultimate strength behavior of cracked ship structural elements are reviewed from different points of views. Methods and parameters involved in ultimate strength of cracked ship structural elements are tabulated in a comparative manner. Influence of various considerations by different authors are explained in details. Summary tables provide convenient means to assess effects of different methods and parameters.